Seven women in The Bath of Remembrance: one narrator and three surrealistic indigenous women in the Amazon (2020)
This study analyses the relationships between intercultural education, women’s painful memories, and collective leadership using an art installation, The Bath. Some of the processes and materials generated during the creation of the installation are presented. This experience of intercultural education in an Amazonian territory is part of a collective process involving a group of indigenous women as well as a team of students and professors, in which I work as a researcher. This experience enabled the generation of a reflection on the conditions for the creation of a collective indigenous female leadership, which is currently very incipient in the country. © 2019, © 2019 Informa UK Limited, trading as Taylor and Francis Group.